2021
DOI: 10.3389/fphar.2021.707891
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Hydrogel, VitroGel® ORGANOID-3, Improves Immune Cell-Epithelial Interactions in a Tissue Chip Co-Culture Model of Human Gastric Organoids and Dendritic Cells

Abstract: Immunosurveillance of the gastrointestinal epithelium by mononuclear phagocytes (MNPs) is essential for maintaining gut health. However, studying the complex interplay between the human gastrointestinal epithelium and MNPs such as dendritic cells (DCs) is difficult, since traditional cell culture systems lack complexity, and animal models may not adequately represent human tissues. Microphysiological systems, or tissue chips, are an attractive alternative for these investigations, because they model functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…These results indicated that all hydrogel properties (both mechanical and biochemical) were favorable to maintain positive hASCs characteristics. Our results are in line with previous studies [ 52 , 53 ], showing different cell types (like immune, epithelial, and stem cells) encapsulated in VG-based hydrogels. The results demonstrated that these hydrogels were interesting matrices able to create a cell-friendly environment.…”
Section: Resultssupporting
confidence: 93%
“…These results indicated that all hydrogel properties (both mechanical and biochemical) were favorable to maintain positive hASCs characteristics. Our results are in line with previous studies [ 52 , 53 ], showing different cell types (like immune, epithelial, and stem cells) encapsulated in VG-based hydrogels. The results demonstrated that these hydrogels were interesting matrices able to create a cell-friendly environment.…”
Section: Resultssupporting
confidence: 93%
“…In addition, higher fidelity of in vitro models has been achieved by vascularization [ 61 , 62 ], multicellular co-culture [ [63] , [64] , [65] ], tissue engineering [ [66] , [67] , [68] ], tissue decellularization [ 69 , 70 ] and genetic technologies [ [71] , [72] , [73] ]. It is expected that more components of the TME will be introduced into PDTOs in the future by applying these methods [ [74] , [75] , [76] ].…”
Section: Discussionmentioning
confidence: 99%
“…These technical advances enable optimizing the organoid cell size and differentiation, thus broadening the range of readout approaches that can be applied to organoids, for example, testing drugs or other host cell–derived secreted factors on disease-modeling organoids (eg, immune mediators). 130 , 131 It therefore is primordial to gather as much information as possible about the ECM biochemical (eg, composition, protein isoforms, signaling growth factors) and physical properties (eg, stiffness) appropriate for the tissue to be modeled. A few recent reviews have compiled advantageous characteristics about currently available animal tissue–derived, or synthetic hydrogels, in their ability to promote and sustain organoid culture.…”
Section: What To Consider When Adapting Organoid-based Models To Unex...mentioning
confidence: 99%